Physical (In)Activity Gender Gap of Slovak Non-athlete Adolescents - Adamčák, Štefan; Marko, Michal; Bartík, Pavol (Physical Education Theory and Methodology, 2023)
Study purpose. Declining levels of physical activity in adolescence are of increasing concern, with data showing the difference of ≥ 8% by gender in favor of adolescent boys; therefore, the present study aims at determining physical (in)activity gender gap of non-athlete adolescent boys and girls in Slovakia. Materials and methods. Standardized measure to estimate the habitual practice of physical activity (IPAQ-SF) was carried out six months (January – June, 2022), through the intentional sampling of 1 517 Slovak non-athlete adolescent boys (40.54%, n = 615) and girls (59.46%, n = 902), aged 18 – 19 years (18.50 ± 0.50 years), attending the secondary schools. Descriptive statistics (e.g., measures of frequency, central tendency), two-sample t-test and chi-square test (x2) were used to analyze and compare the data. Results. When considering the physical activity (seven-day week) in adolescence, the Slovak non-athlete adolescent boys and girls reported: (i) high levels of physical activity – 51.73% (n = 785); (ii) moderate levels of physical activity – 25.92% (n = 393); (iii) low levels of physical activity – 22.35% (n = 339) (p ˂ 0.01). When considering the gender gap in physical activity in adolescence, total physical activity (seven-day week), expressed in MET-minutes/ week, was lower (statistically, p ˂ 0.01; difference of 712 MET-minutes/ week) among the Slovak non-athlete adolescent girls (1 898 MET-minutes/ week), compared to boys (2 610 MET-minutes/ week). And when considering the gender gap and sitting time (sedentary behavior), the Slovak non-athlete adolescent girls were more sedentary, compared to boys (p ˃ 0.05) (360 vs. 330 minutes/ week). Conclusions. Constant low levels of physical activity in adolescence constitute the public health emergency of international concern; therefore, the urgent policy action to increase the physical activity is necessary; in particular, in promoting and retaining the adolescent girls’ participation in physical activity.